PENGARUH SENAM FANTASI TERHADAP PERKEMBANGAN MOTORIK KASAR ANAK PADA (4-6 TAHUN) - Ratu Disa Rozanatul Huda; Ria Setia Sari; Febi Ratnasari (Nusantara Hasana Journal, 2021)
Gross motor development (gross motor) is the control of the body through coordinated activity between the nervous system, brain, brain and spinal cord. Fantasy gymnastics is a play activity of activities that fantasize by using methods that emphasize the child’s imagination. This type of literature review includes research studies where most research studies are published in specialized journal of libraries. In several searches of this literature article using two languages namely Indonesian and English, the respondents are children aged 4-6 years and are vulnerable in this article 5 years (2015-2020). Based on this literature review of 20 articles found there is a relationship between fantasy gymnastics and the gross motor development of children. So, children who do gymnastics fantasy motor development can increase. The conclusion of this literature review showed that the gross motor development of children could increase completely so the children had to do the effect of gymnastics/games. Therefore, children aged 4-6 years should be trained in their gross motor system, since without doing the training before, many children lack their achievement in gross motor.